To Determine the Decision to Delivery Interval in Category I Emergency Caesarean Sections in A Tertiary Care Hospital of Peshawar - Maimoona Qadir Khan; Fauzia Afridi; Mehjabina S.Ghayur (Gandhara University, 2023)
OBJECTIVES The aim of our study is to determine the exact timing of the decision to the delivery interval in grade I caesarean sections, the factors contributing to the delays and the indications of those caesarean sections. METHODOLOGY This descriptive(cross-sectional) study is conducted in the Gynae B unit of Khyber Teaching Hospital, Peshawar from 1st April 2020 to 30th September 2020 over a span of 6 months. It is a consecutive non-purposive sampling. All women of any age or parity who underwent an emergency grade I caesarean section were included in the study. Age, gestational age, booking status, obstetrical history, the decision to delivery interval, an indication of caesarean, and mode of anesthesia was noted and entered in predesigned proforma. RESULTS 114 patients underwent grade I caesarean in the study period.61(54%) were 21-30 years age group and 48(42%) were in the 31-40 years age group.26(23%) patients were not delayed.31(27%) got delayed as Operation Theatre table was not available,18(16%) could not arrange Caesarean medication and consumables in time,17(15%) could not provide preop investigations in time, in 13(11%) cases patient's attendants were not available. Fetal distress was the most common cause (33%) of delayed caesarean sections, followed by previous scars in labour (20%), placenta previa with APH (13%), obstructed labour (12%), placental abruption and CPD in labour in 8% each. Spinal anaesthesia was given in 79% and General anaesthesia was given in 21% of cases. CONCLUSION 26(23%) patients were not delayed and their decision to deliver interval was less than 30 minutes. The decision to the delivery interval in Khyber Teaching Hospital was far longer than recommended. The leading causes are delayed arrangement of the OT table, OT stuff and investigations.